2014
DOI: 10.1111/jipb.12179
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative genetic analysis of chlorophyll a fluorescence parameters in maize in the field environments

Abstract: Chlorophyll fluorescence transient from initial to maximum fluorescence ("P" step) throughout two intermediate steps ("J" and "I") (JIP-test) is considered a reliable early quantitative indicator of stress in plants. The JIP-test is particularly useful for crop plants when applied in variable field environments. The aim of the present study was to conduct a quantitative trait loci (QTL) analysis for nine JIP-test parameters in maize during flowering in four field environments differing in weather conditions. Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…It is possible that the authors erroneously used the 50-µs point for the F O value of the OJIP measurements, but it may also suggest that there were methodological problems. Šimić et al (2014) studied 205 recombinant inbred lines of the cross of the maize lines B73 × M017 in four environmental conditions differing in soil moisture levels. The authors used the following parameters for screening: TRo/ABS, ETo/TRo, ABS/RC, TRo/RC, ETo/RC, DIo/RC, TRo/DIo, ETo/(TRo − ETo), PI abs .…”
Section: Question 29: Can Fluorescence Parameters Be Used For Qtl Stumentioning
confidence: 99%
“…It is possible that the authors erroneously used the 50-µs point for the F O value of the OJIP measurements, but it may also suggest that there were methodological problems. Šimić et al (2014) studied 205 recombinant inbred lines of the cross of the maize lines B73 × M017 in four environmental conditions differing in soil moisture levels. The authors used the following parameters for screening: TRo/ABS, ETo/TRo, ABS/RC, TRo/RC, ETo/RC, DIo/RC, TRo/DIo, ETo/(TRo − ETo), PI abs .…”
Section: Question 29: Can Fluorescence Parameters Be Used For Qtl Stumentioning
confidence: 99%
“…Björkman and Powles (1984) reported that there were no inhibition of electron-transport activity in shade grown plants even when leaf water potential was low (3.0 MPa) and the degree of inhibition under more severe water stress was much less pronounced than in the plants kept in full daylight. Photoinhibitory effect of the interaction between high light and drought was demonstrated in many publications (Akashi et al, 2008;Šimić, Lepeduš, Jurković, Antunović, & Cesar, 2014), while less is known about the interaction of low light (less than 100 μmol m -2 s -1 ) and drought stress (Dinakar, Djilianov, & Bartels, 2012;Yang, Han, Liu, Lin, & Wang, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthetic efficiency at different water contents was studied in many plant species such as barley, maize, soybean, winter wheat, etc. (OUKARROUM et al, 2009;HAO et al, 2013;ŠIMIĆ et al, 2014). Common method for investigation of photosynthetic efficiency is measurement of chlorophyll a fluorescence which is used for identifying differences in plant photosynthetic performance in rapid and nondestructive way (ŽIVČÁK et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this research, tolerance to different soil water contents of sunflower genotypes was evaluated by the maximum quantum yield of photosystem II (Fv/Fm), photosynthetic performance index (PIABS) and measured leaf temperature values. Fv/Fm provides information about the proportion of the light absorbed by chlorophyll in photosystem II and PIABS gives information on overall energy flow through photosystem II (ŠIMIĆ et al, 2014).…”
Section: Introductionmentioning
confidence: 99%